Concussion history`s impact on stability evaluation test scores in male division I lacrosse and football players - Miyashita, T.; Holland, B.; Diakogeorgiou, E.; Cochrane-Syman, K. (The Journal of Sports Medicine and Physical Fitness, 2025)
BACKGROUND: Concussion baseline testing is standard practice in collegiate athletes. The influence of concussion history on balance performance remains pervasive, especially with computerized, quantified measures. The aim of this study was to explore concussion history on baseline balance measures.